Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania

Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.

Functional and disordered meso-macroporous gamma-Al2-xMxO3 +/- y (M = Cu and/or Ce) - Gnanakumar, Edwin S.; John, Jino C.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2013)
Disordered meso-macro porous Cu-Ce-Al2O3 nanocomposite (gamma-Al2-xMxO3 +/- y, M = Cu and or Ce) with different compositions has been synthesized. In situ templated sol-gel method has been adopted with simple EDTA ethylenediamine tetra aceticacid and ethylenediamine molecules to prepare gamma-Al2-xMxO3 +/- y, (M = Cu and or Ce). Above meso-macro porous materials were characterized by structural, spectroscopy, microscopy and textural techniques. Detailed characterization indicates that Cu2+ ions are introduced into the ceria and alumina lattice positions. Nano composite nature of the gamma-Al2-xMxO3 +/- y has been confirmed by detailed microscopy investigations. Catalytic activity of the above nanocomposite materials have been screened for environmentally important CO oxidation reaction. 30% Ce-60% Al and 10% Cu containing material shows the best activity among other meso-nnacroporous material with (50%) 100% CO oxidation at (107 degrees C) 145 degrees C.
Keywords: Alumina; CO oxidation; heterogeneous catalysis; Meso-Macroporous Material; Nanocomposite; Sol-gel synthesis

Oxidative dehydrogenation of ethyl benzene to styrene over hydrotalcite derived cerium containing mixed metal oxides - Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Kaliyappan, Periyasamy; Raja, Thirumalaiswamy (Green Chemistry, 2013)
Cerium containing mixed oxides derived from hydrotalcites was prepared and its catalytic activity was studied for oxidative dehydrogenation of ethyl benzene to styrene. Structural, spectroscopic and morphological features of the catalyst have been thoroughly examined with various physico-chemical characterization methods. Raman spectroscopy studies show evidence for oxygen vacancies in lower loadings of cerium which enhanced the oxygen migration. The transmission electron microscopy image showed good dispersion of ceria clusters on the mixed metal oxide. The catalytic activity results suggested that the conversion of ethyl benzene and styrene yield is stable for at least 12 hours without any significant catalyst deactivation. The styrene selectivity and ethyl benzene conversion were higher in a catalyst containing 0.03 mole percentage of cerium. Structural features of the spent catalysts have also been examined to demonstrate the stability of the catalyst during the reaction.

Green chemistry approach to styrene from ethylbenzene and air on MnxTi1-xO2 catalyst - Negi, Sanjay Singh; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy; Singh, Anand Pal; Gopinath, Chinnakonda S. (RSC Advances, 2014)
Styrene (ST) is an industrially important commodity chemical, and design of a suitable catalyst, which provides high ethyl benzene (EB) conversion and styrene selectivity at Lower temperature with sustainable activity, is one of the major challenges in the field of heterogeneous catalysis. Manganese incorporated in titania (MnxT1-xO2) anatase Lattice, prepared via the solution combustion method, was evaluated for oxidative dehydrogenation (ODH) of EB with O-2 or air. MnxTi1-xO2 catalysts were characterized by different physiochemical methods. Up to 15% Mn could be introduced into the TiO2 Lattice. TEM and XRD indicate disordered mesoporosity, further confirmed by adsorption isotherm analysis. MnxTi1-xO2 catalysts were evaluated for ST synthesis from EB using air or oxygen as oxidant between 440 and 570 degrees C. Reaction conditions have been varied systematically, such as catalyst composition, and EB/air/O-2 flow. MnxTi1-xO2 shows sustainable 55% styrene yield for 45 h without deactivation under optimum conditions. A thorough analysis of spent catalysts demonstrates the conversion of initial anatase phase MnxTi1-xO2 to Mn3O4 supported on the rutile (R) phase of TiO2. The above change occurs in the first few hours of reaction and the Mn3O4 on R-TiO2 phase is the active phase of the catalyst and responsible for sustainable activity for Longer duration.

Investigations into variations in local cationic environment in layered oxide series InGaO3(ZnO)(m) (m=1-4) - Narendranath, Soumya B.; Yadav, Ashok Kumar; Ajithkumar, Thalasseril G.; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Dey, Krishna K.; Raja, Thirumalaiswamy; Devi, R. Nandini (Dalton Transactions, 2014)
Layered oxides of the series InGaO3(ZnO)(m) (m = 1-4) are interesting due to their structural anisotropy. Here, we report a comprehensive study of their structural details, focusing on the local cationic environment in bulk powder samples by MASNMR and EXAFS, which is hitherto not attempted. It is found that the Ga geometry varies gradually from pure pentacoordinated to a mixture of penta and tetracoordinated with increasing amounts of tetracoordination as we move across the series, contrary to previous reports suggesting exclusively trigonal bipyramidal coordination in all the compounds. A similar observation is also made in the case of Zn and structural evolution involving the dissolution of Ga in a ZnO4 tetrahedral network in a sandwich layer can be discerned, as the insulating ZnO layer size increases.

Role of nanointerfaces in Cu- and Cu plus Au-based near-ambient-temperature CO oxidation catalysts - Gnanakumar, Edwin S.; Naik, Jarpla Madhusudhan; Manikandan, Marimuthu; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Disordered mesoporous Cu-doped ceria-zirconia (Cu0.1Ce0.85Zr0.05O2), and gold deposited (Au/Cu0.1Ce0.85Zr0.05O2) catalysts were synthesized and evaluated for CO oxidation. Onset of CO oxidation activity, and 50% (100%) CO2 formation occurs at room temperature (RT), and 77 (120)degrees C, respectively, with Cu0.1Ce0.85Zr0.05O2. A small amount of gold on Cu0.1Ce0.85Zr0.05O2 induces the sustainable oxidation catalysis around RT. Onset of copper reduction temperature decreases from 110 degrees C on Cu0.1Ce0.85Zr0.05O2 to 48 degrees C with Au/Cu0.1Ce0.85Zr0.05O2, highlighting the direct interaction between Cu and Au through a Cu-Au interface. Au particles with a (00 1) facet deposit on an oxygen-deficient site of (111) facet of CeO2-ZrO2. Any decrease in surface Cu-content with increasing Au-content further supports the Au-Cu-Ce/Zr interface interactions. Nanointerfaces of Au clusters on Cu next to oxygen-deficient sites of CeO2-ZrO2 facilitate all the elementary steps of the CO + O-2 reaction to occur in close proximity at ambient conditions.
Keywords: carbon monoxide; Gold; heterogeneous catalysis; Oxidation; redox

Efficient robust fluorite CeZrO4-delta oxide catalyst for the eco-benign synthesis of styrene - Periyasamy, Kaliyappan; Aswathy, Venugopalan T.; Kumar, Venugopal Ashok; Manikandan, Marimuthu; Shukla, Rakesh; Tyagi, Avesh K.; Raja, Thirumalaiswamy (RSC Advances, 2015)
In this work, we have reported CeO2, ZrO2, physically mixed (PH)-CeO2/ZrO2 and fluorite CeZrO4-delta oxides and their catalytic activities for the oxidative dehydrogenation (ODH) of ethyl benzene (EB) to styrene (ST) using molecular oxygen, air and carbon dioxide as oxidants. The catalysts were prepared by a gel-combustion method followed by calcination at 600 degrees C for 6 h and subjected to catalytic activity measurements. All the catalysts were characterized and studied by various physicochemical methods. The reaction parameters were varied systematically such as different catalysts, oxidants, temperatures, EB flow and oxidant flow. CeZrO4-delta accounted for a 47% styrene yield for 72 h without any significant deactivation under optimized reaction conditions. A thorough analysis of the spent catalysts demonstrated the robustness of the catalyst for this reaction under different oxidants and reaction conditions. Pristine CeO2 deactivated easily and the activity decreased with time on stream of the reaction.

M-Au/TiO2 (M = Ag, Pd, and Pt) nanophotocatalyst for overall solar water splitting: role of interfaces - Melvin, Ambrose A.; Illath, Kavya; Das, Tanmay; Raja, Thirumalaiswamy; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (Nanoscale, 2015)
M-Au/TiO2 (M = Ag, Pd, Pt) composites were prepared through a facile one-pot photodeposition synthesis and evaluated for solar water splitting (SWS) with and without a sacrificial agent. The M-Au combination exhibits a dominant role in augmenting the H2 generation activity by forming a bi-metallic system. Degussa P25 was used as a TiO2 substrate to photodeposit Au followed by Au + M (M = Ag/Pd/Pt). The SWS activity of the M-Au/TiO2 was determined through photocatalytic H-2 production in the presence of methanol as a sacrificial agent under one sun conditions with an AM1.5 filter. The highest H-2 yield was observed for Pt-0.5-Au-1/TiO2 and was around 1.3 +/- 0.07 mmol h(-1) g(-1), with an apparent quantum yield (AQY) of 6.4%. Pt-0.5-Au-1/TiO2 also demonstrated the same activity for 25 cycles of five hours each for 125 h. Critically, the same Pt-0.5-Au-1/TiO2 catalyst was active in overall SWS (OSWS) without any sacrificial agent, with an AQY = 0.8%. The amount of Au and/or Pt was varied to obtain the optimum composition and it was found that the Pt0.5-Au1/TiO2 composition exhibits the best activity. Detailed characterization by physico-chemical, spectral and microscopy measurements was carried out to obtain an in-depth understanding of the origin of the photocatalytic activity of Pt-0.5-Au-1/TiO2. These in-depth studies show that gold interacts predominantly with oxygen vacancies present on titania surfaces, and Pt preferentially interacts with gold for an effective electron-hole pair separation at Pt-Au interfaces and electron storage in metal particles. The Pt in Pt-0.5-Au-1/TiO2 is electronically and catalytically different from the Pt in Pt/TiO2 and it is predicted that the former suppresses the oxygen reduction reaction.

Effective and selective oxidation of 2-butanol over Mn supported catalyst systems - Prabu, Kandasamy; Prabu, Marimuthu; Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Sandilya, W. V. Y. Sai; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (Applied Catalysis A-General, 2016)
Oxidation of alcohols to their corresponding aldehydes/ketones is an important reaction in industries as well as in academic perspective. Selective oxidation (Selox) of alcohols like methanol, ethanol and propanol are well studied in literature; however, alcohols like butanol, pentanol, octanol is a challenging task. Selective oxidation of 2-butanol to methyl ethyl ketone (MEK) is an important reaction due to its wide range of applications. Herein, we demonstrated the selective oxidation of 2-butanol to MEK over Mn supported on different oxide supports. A series of MnxOy-Al2O3 (MA), MnxOy-CeO2 (MC), MnxOy-ZrO2 (MZ) and MnxOy-SiO2 (MS) catalysts were prepared by co-precipitation followed by hydrothermal method. As synthesised catalysts were characterised by various physico-chemical characterisation techniques. It was found that the presence of Mn3O4 species in MA and MZ catalysts is responsible for maximum catalytic activity towards 2-butanol oxidation. MA catalyst conferred a maximum 2-butanol conversion of 51% and 88% selectivity towards MEK. XPS analysis revealed that Mn in MA catalyst exists in +2 and +3 oxidation states and responsible for 2-butanol oxidation. Moreover it was found that the acidity of the catalyst also plays an important role in catalytic activity. (C) 2016 Published by Elsevier B.V.

Promotional effect of Fe on the performance of supported Cu catalyst for ambient pressure hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Nagpure, Atul S.; Chilukuri, Satyanarayana V.; Raja, Thirumalaiswamy (RSC Advances, 2016)
A noble-metal free FeCu based bimetallic catalyst system prepared by facile co-impregnation method was found to be highly admirable for vapour phase selective hydrogenation of furfural to furfuryl alcohol at ambient pressure. Monometallic Cu/gamma-Al2O3, Fe/gamma-Al2O3 and bimetallic FeCu/gamma-Al2O3 catalysts with different Fe loadings were prepared. Structural and morphological features of the catalysts were thoroughly investigated by several physico-chemical characterization techniques. The influence of various reaction parameters, such as Fe loading, reaction temperature and flow of reactants was examined with respect to furfural conversion and furfuryl alcohol yield. The results clearly showed that an optimum amount of Fe is necessary to enhance the catalytic activity of monometallic Cu/gamma-Al2O3 for the selective hydrogenation of furfural. The catalyst FC-10 with 10 wt% Fe exhibited excellent activity which led to high furfural conversion (>93%) and furfuryl alcohol selectivity (>98%) under mild reaction conditions. The higher activity of bimetallic FeCu/gamma-Al2O3 compared to monometallic Cu/gamma-Al2O3 is ascribed to the formation of FeCu bimetallic particles and the existence of oxygen vacancies in the Fe oxide system. The superior activity after Fe loading on the Cu-based catalyst was attributed to the synergy between Cu and Fe. A plausible mechanism is proposed to explain the promoting effect of Fe, which involves synergism between Fe sites with strong oxophilic nature and Cu sites with a high ability for hydrogen activation. Based on the activity results, prolonged catalytic activity and spent catalyst analysis, the developed FeCu/gamma-Al2O3 catalyst is inexpensive, eco-benign and robust, which makes it a promising candidate for the efficient conversion of biomass-derived substrates to fine chemicals and drop-in biofuels.

Molybdenum carbide catalyst for the reduction of CO2 to CO: surface science aspects by NAPPES and catalysis studies - Reddy, Kasala Prabhakar; Dama, Srikanth; Mhamane, Nitin B.; Ghosalya, Manoj K.; Raja, Thirumalaiswamy; Satyanarayana, Chilukuri V.; Gopinath, Chinnakonda S. (Dalton Transactions, 2019)
Carbon dioxide is a greenhouse gas, and needs to be converted into one of the useful feedstocks, such as carbon monoxide and methanol. We demonstrate the reduction of CO2 with H-2 as a reducing agent, via a reverse water gas shift (RWGS) reaction, by using a potential and low cost Mo2C catalyst. Mo2C was evaluated for CO2 hydrogenation at ambient pressure as a function of temperature, and CO2 : H-2 ratio at a gas hourly space velocity (GHSV) of 20 000 h(-1). It is demonstrated that the Mo2C catalyst with 1 : 3 ratio of CO2 : H-2 is highly active (58% CO2 conversion) and selective (62%) towards CO at 723 K at ambient pressure. Both properties (basicity and redox properties) and high catalytic activity observed with Mo2C around 700 K correlate well and indicate a strong synergy among them towards CO2 activation. X-ray diffraction and Raman analysis show that the Mo2C catalyst remains in the beta-Mo2C form before and after the reaction. The mechanistic aspects of the RWGS reaction were determined by near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) with in situ generated Mo2C from carburization of Mo-metal foil. NAPXPS measurements were carried out at near ambient pressure (0.1 mbar) and various temperatures. Throughout the reaction, no significant changes in the Mo2+ oxidation state (of Mo2C) were observed indicating that the catalyst is highly stable; C and O 1s spectral results indicate the oxycarbide species as an active intermediate for RWGS. A good correlation is observed between catalytic activity from atmospheric pressure reactors and the electronic structure details derived from NAPXPS results, which establishes the structure-activity correlation.

Phase transfer ceria-supported nanocatalyst for nitrile hydration reaction - Gupta, Nikitra N.; Punekar, Amrin S.; Raj, Karthik Raja E. K.; Ghodekar, Medha M.; Patil, Vipul S.; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (ACS Omega, 2019)
The present study elaborates the catalytic effect of rare-earth metal oxides (Sm2O3 and La2O3) over ceria as a support phase transfer catalyst. The synthesized catalysts have been subjected to different characterization techniques, such as field-emission scanning electron microscopy, high-resolution transmission electron microscopy, powder X-ray diffraction, N-2 adsorption-desorption (BET surface analysis), temperature-programmed desorption study (NH3/CO2-TPD), Fourier transform infrared, Raman analysis, and X-ray photoelectron spectroscopy to get better insights into the catalytic activity of the catalysts for hydration of nitrile.

Synthesis of biodiesel using the Mg/Al/Zn hydrotalcite/SBA-15 nanocomposite catalyst - Prabu, Marimuthu; Manikandan, Marimuthu; Kandasamy, Prabu; Kalaivani, P. R.; Rajendiran, Nagappan; Raja, Thirumalaiswamy (Acs Omega, 2019)
Biodiesel production is an enchanting and eccentric pathway for the reduction of use of fossil fuels and is procured from biologically available renewable sources such as oils and fats. A novel Mg/Al/Zn-based hydrotalcite/SBA-15 composite material having a high catalytic activity was developed and investigated for the transesterification of vegetable oil. The rationally developed composites were systematically characterized and assessed in the transesterification of soybean oil in the presence of methanol. The physicochemical evaluation of the nanocomposites demonstrated the influence of Zn in the textural characteristics, density of the basic sites, and successively the catalytic activity. The catalytic efficiency of the MAZ-x/SBA-15 composite could be linked with the basic site density determined by the temperature-programmed desorption of CO2. Among all the composites used, the MAZ-1/SBA-15 nanocomposite showed the highest activity for biodiesels, with a yield of around 90% under economical reaction conditions. The catalytic studies conferred that the fatty acid methyl ester yield is significantly influenced by various experimental conditions such as the catalyst molar ratio, reaction temperature, pressure, and contact time. It was also found that the incorporation of hydrotalcite into SBA-15 pore channels can enhance the catalyst efficiency and stability of the nanocomposite. Moreover, under mild reaction conditions, a remarkably stable catalytic performance was achieved for more than 200 h of time on stream with no catalyst deactivation.

Controlling and stabilization of Ru nanoparticles by tuning the nitrogen content of the support for enhanced H-2 production through aqueous-phase reforming of glycerol - Gogoi, Pranjal; Kanna, Narsimharao; Begum, Pakiza; Deka, Ramesh C.; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (ACS Catalysis, 2020)
The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H-2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H-2. Nitrogen-doped mesoporous carbons (NMCs) were utlized as supports and found to have a strong influence on the catalytic performance of the catalysts. Incorporation of nitrogen in the carbon framework significantly enhanced the catalytic activity compared to Ru catalysts on nitrogen-free supports. Notably, the catalyst (5 wt % Ru-NMC-3) with optimal N content (10.9 wt %) demonstrated improved stability and H-2 selectivity, which are better than those of many state-of-the-art catalysts. Nitrogen in the carbon framework has a dual relationship with the activity of the catalyst: (i) it creates basic environment over the catalysts support and (ii) it acts as an anchoring site for metal nanoparticles. Anchoring of metal nanoparticles has helped to curb their sintering, thus leading to better stability of the catalysts under APR reaction conditions. Various characterization techniques were employed to understand the nature of active catalytic sites responsible for higher H-2 production while minimizing CO formation. In situ CO-FTIR studies showed that the higher catalytic activity of 5 wt % Ru-NMC-3 catalyst was attributed to the enhanced WGS activity over this catalyst. Density functional theory calculations were performed to understand the stabilization of metal nanoparticles by different types of N present on the support and provide insights into the prefered sites of glycerol adsorption on the NMC support. Since S wt % Ru-NMC-3 was the relatively best catalyst, it was selected for the preparation of bimetallic catalysts. Accordingly, addition of Pt to this system helped to increase the stability of the catalyst. This bimetallic catalyst may, therefore, find application for wide use in APR of biomass oxygenates.
Keywords: aqueous-phase reforming; Glycerol; H-2 production; Ru/NMC catalyst; synergistic effect

Insights into the catalytic activity of Ru/NaY catalysts for efficient H-2 production through aqueous phase reforming - Gogoi, Pranjal; Nagpure, Atul S.; Kandasamy, Prabu; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (Sustainable Energy & Fuels, 2020)
Ruthenium nanoparticles supported on NaY zeolite catalysts were synthesized by a simple ion exchange method. The structural and morphological features of the catalysts were systematically investigated using numerous techniques such as N-2-sorption, XRD, CO2-TPD, H-2-TPR, TEM, SEM, ICP-OES, TGA, CHN analysis, XPS, in situ CO-FTIR and NMR spectroscopy. These novel Ru-NaY catalysts were highly active and selective for H-2 production through aqueous phase reforming (APR) of glycerol and ethylene glycol. Among the various catalysts evaluated for H-2 production, the 3 wt% Ru-NaY catalyst demonstrated the highest catalytic performance with excellent H-2 selectivity and this catalyst exhibits better activity as compared to many state of the art catalysts reported so far. The superior catalytic activity of 3 wt% Ru-NaY was attributed to the appropriate Ru metal loading, good metal dispersion, small size of Ru nanoparticles, better metal-support interaction, and higher availability of catalytically active sites (Ru-0) and facilitated water gas shift (WGS) reaction. This catalytic activity result clearly shows that NaY zeolite supported Ru nanoparticles catalysts have excellent potential for H-2 production from biomass-derived compounds.

Highly efficient and reusable Ru-NaY catalyst for the base free oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic acid - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy (Catalysis Today, 2021)
Oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is an important reaction for the production of recyclable bio-based polymers. Herein, we report a series of Ru nanoparticles supported on NaY zeolites catalysts for the oxidation of HMF to FDCA. The catalysts were prepared by simple ion exchanged method. Among all the catalysts, the optimized 3 wt % Ru-NaY catalyst showed superior catalytic activity under base free conditions with a shorter period of reaction time. The conversion of HMF was 100 % with 94 % FDCA yield. This catalyst was reused for fourth cycles, with an insignificant decrease in the yield of FDCA. H2-chemisorption and HRTEM studies confirmed that high metal dispersion and small size of Ru nanoparticles play vital roles for the HMF oxidation. In addition, the acidic hydroxyl groups of the supercage as well as higher amount of metallic Ru° are also responsible for the high yield and productivity of FDCA.

Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15

Green synthesis of cyclohexanone to adipic acid over Fe-W oxides incorporated mesoporous carbon support - Mekala, Siva Prasad; Prabu, Marimuthu; Gawali, Sheetal Datta; Gopakumar, Karthik; Gogoi, Pranjal; Bhatkar, Akash Ravindra; Mohapatra, Gourab; Unnikrishanan, Eeswar; Raja, Thirumalaiswamy (Catalysis Communications, 2022)
We have prepared iron and tungsten oxides incorporated mesoporous carbon (MC) catalysts using a simple hydrothermal methodology with different carbon sources, and the catalytic performance was investigated for cyclohexanone oxidation. An adequate amount of metal oxide loading has displayed a key role in the selective catalyst for adipic acid (AA) synthesis. The MC catalyst has shown its prime activity under the influence of redox properties of W5+/W6+ and Fe2+/Fe3+ as promoters. The 10%Fe 90%W-MC fructose as a carbon source catalyst has provided its best selectivity of 87% for AA at 120 ?C.
Keywords: Adipic Acid; Liquid phase oxidation; mesoporous carbon; Redox center

Sustainable CO2 reduction on in (2)O(3 )with exclusive CO selectivity: catalysis and in situ valence band photoelectron spectral investigations - Mhamane, Nitin B.; Chetry, Sibo; Ranjan, Ravi; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2022)
This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H-2 ratios exhibit 98-99.6% CO selectivity with 25-38% CO2 conversion between 773 and 873 K. CO2 and H-2 conversion under steady-state conditions at 773-873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H-2 feed) on the catalyst surface, underscoring the presence of an ideal reactant composition for the reverse water-gas shift reaction, while H-2-rich feed compositions show the H-2-dominated surface. Surface electronic structure changes, under near-operating conditions, were explored with near ambient pressure photoelectron spectroscopy (NAPPES), and the interesting findings are as follows: (a) A shift in the valence band to lower binding energy, up to 0.6 eV, was observed because of electron filling at high temperatures. (b) An observation of heterogeneous nature of the catalyst surface under NAPPES measurement conditions is attributed to the generation of active oxygen vacancy (O-v) sites, which in turn changes the work function of In2O3. (c) The above changes are found to be reversible, when the reaction was stopped. Vibrational features of the reactant molecules were observed to be broadened in the active temperature window of the catalyst supporting the heterogeneous character of the catalyst surface because of dynamic O-v generation. By optimizing gas hourly space velocity, CO2:H-2 ratio, and reaction temperature, exclusive CO selectivity is possible with a H-2:CO2 ratio of similar to 0.67, which will avoid the product separation stage altogether, while minimizing the expensive H-2 in the reactant feed.
Keywords: heterogeneous catalysis; Oxygen vacancy; photoelectron spectroscopy; RWGS; Work function

Tailoring the properties of Ni(111)/graphone interfaces by intercalation of Al and Na: a DFT study - Archana, Ramakrishnan; Joshi, Niharika; Raja, Thirumalaiswamy (C-Journal of Carbon, 2022)
With the incredible discovery of graphene (Gr), all of the properties studied to date suggest that it has promising applications in the development of semiconductor, spintronic, insulating, and polymer materials. However, efforts are still underway to fully understand the nature of metal–graphone(GrH) interaction in order to offer better scope for tuning the electronic and magnetic properties, which can be performed by intercalation of atoms via metal support on graphene. We chose metal atoms belonging to the s and p blocks, namely Na and Al, respectively, as the intercalating atoms. Herein, the maximum coverage of a monolayer of Na and Al was comparatively studied on a Ni(111) surface. Significant changes in the magnetic and electronic properties at the Ni(111)/graphone interface were observed upon intercalation. Of the two intercalating metal atoms, Na proved to be more effective, such that the magnetic properties of the surface Ni were only slightly decreased, and the graphone also showed better magnetic properties than in the absence of Na.

Co3O4 for sustainable CO2 reduction and possible fine-tuning towards selective CO production - Ranjan, Ravi; Tekawadia, Jyoti; Jain, Ruchi; Mhamane, Nitin B.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2023)
Two main challenges involved in heterogeneous catalytic CO2 reduction are: (a) decreasing the consumption of H2 to the minimum required level with possibly the maximum CO2 conversion, and (b) concurrently enhancing the selectivity of the desired CO, at the cost of methane. Towards meeting these two challenges, Co3O4 spinel has been identified as a potential catalyst and it exhibits predominant CO selectivity > 673 K at atmospheric pressure. CO2 conversion begins > 523 K, with 100% CO selectivity observed > 673 K with CO2:H2 = 3:2. Current work shows a sustainable catalytic CO2 conversion to 100% CO selectivity with Co3O4-Nanocube (NC). Critically, CO selectivity and yield is observed to increase at the cost of methane with smaller amount of H2. 1:1 and 3:2 CO2:H2 ratio exhibits 88-100% CO selectivity with 24-32.5% CO2 conversion between 623 and 823 K. Irrespective of the input CO2:H2, ratio of CO2:H2 uptake changes from around 1:3 at 523 K to 1:1-1.5 at 823 K with concurrent production of significant methane to predominant CO, respectively. Surface electronic state changes was explored by near ambient pressure photoelectron spectroscopy, and the results suggests that Co3O4 is the active phase that promotes CO2 reduction selectively to CO. Broadening observed with the vibrational feature of the CO2 molecules at high temperature underscores the heterogeneous character of the catalyst surface, under operating conditions, due to changing electron density. By optimizing the gas hourly space velocity (GHSV), H2-lean CO2:H2 ratio, and the reaction temperature/pressure, 100% CO selectivity could be broadened to a range of operating conditions.
Keywords: Carbon neutral economy; heterogeneous catalysis; RWGS; SDG; Surface Science

MnXWO4 nanostructure-based catalysts for single-step oxidation of cyclohexane and methane to oxygenates - Prabu, Marimuthu; Manikandan, Marimuthu; Samal, Pragnya Paramita; Gurrala, Lakshmi Prasad; Mekala, Siva Prasad; Archana, Ramakrishnan; Nayak, Chandrani; Bhattacharyya, D.; Jha, S. N.; Krishnamurty, Sailaja; Raja, Thirumalaiswamy (ACS Applied Nano Materials, 2023)
Activation of the C-H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on MnxWO4 nanostructures within 6 h. The recyclability test confirmed the catalyst heterogeneity, which revealed no appreciable loss of catalytic activity even after three consecutive reactions. In situ DRIFT study reveals that CYH is oxidized to cyclohexanone and cyclohexanol (KA oil) and is further oxidized to AA via carboxylate intermediates. DFT studies disclosed that MnOx species are responsible for the C-H activation of CYH, and the Mn2+/Mn3+ redox centers play a vital role in the absorption of KA oil to form AA. Herein, we demonstrated the significant role of the ``MnOx'' species and that adequate Lewis and Bronsted acidic sites, redox centers of (Mn2+/Mn3+), and lattice oxygen are accountable for the CYH conversion toward the AA. Additionally, we have reported the oxidation of methane to methanol (146 mu mole per gram of catalyst) in the presence of water at 75 degrees C without over-oxidation products.
Keywords: Adipic Acid; C-H bond activation; Cyclohexane oxidation; methane activation; MnOx chain; Redox center

Nitric acid free cyclohexane to adipic acid production using nickel and vanadium incorporated AlPO-5 molecular sieve - Prabu, Marimuthu; Sharma, Shweta; Raja, Abhishekram; Archana, Ramakrishnan; Samruddhi, Mane; Raja, Thirumalaiswamy (Molecular Catalysis, 2023)
Rationally designing a stable and sustainable metal oxide supported over the molecular sieve catalysts for oxidizing cyclohexane (CYH) to adipic acid (AA) is vital in industrial applications. The in-situ hydrothermal synthesis method successfully incorporated vanadium and nickel into the aluminium phosphate-5 (AlPO-5) molecular sieves (MFI structure). The XPS and NH3 TPD analysis disclosed that the addition of Ni into V-AlPO-5 stabilizes the ratio of V4+/V5+, creating strong acidic sites and the formation of NiOOH, which are a vital role for the selective CYH oxidation to AA. An in-situ DRIFT study reveals that nickel takes part in the formation of dicarboxylate ions as an intermediate to form AA. Our catalytic studies profoundly suggested that the Ni0.1V0.2AlPO-5 catalyst used for CYH oxidation gives better selectivity towards AA (53%) in the presence of oxygen at an appropriate amount of solvent without an initiator or promoter within a short time (3h).
Keywords: Adipic Acid; Cyclohexane oxidation; In situ DRIFT; NiOOH; NiVAlPO-5; Ratios ofV4+; V5+

An effective, facile, and rapid synthesis of nanosized Mn3O4 using a microwave route - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Kamble, Aditi; Vaishnav, Vishal; Bogalera, Shivamurthy P.; Manikandan, Marimuthu; Nayaka, Girish Praveen; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Nanoparticle Research, 2024)
Microwave-assisted one-pot, one-step, calcination-free synthesis of nanosized Mn3O4 is reported using only benzylamine and manganese acetate. Benzylamine in this protocol plays a vital role for efficient microwave synthesis. This microwave method enables the synthesis of nanosized Mn3O4 in just few hours only in a single step eliminating the need of calcinations of any intermediate. The synthesized nanosized Mn3O4 was analyzed by XRD, HRTEM, EDAX, and Raman spectroscopy. The catalytic and electrochemical properties of as-synthesized Mn3O4 were investigated. In galvanostatic charge-discharge experiments, after 800 cycles, more than 89% capacitance was retained for electrodes made by as synthesized Mn3O4 nanomaterials indicating its very good stability. In the catalytic conversion of cinnamyl alcohol to cinnamaldehyde via oxidation, using as prepared nanosized Mn3O4 as a catalyst, it displays effective catalytic properties. A probable mechanical study of its formation was also envisaged. This synthesis protocol is additive-free, occurs in a short time, is facile, is energy efficient, and eliminates the use of many chemicals. These silent features make these reported protocols economically viable and environmentally benign which adhere to the principles of Green Chemistry.
Keywords: Calcination free; Electrochemical and catalytic properties; Nanosized Mn3O4; Single-step synthesis

New insights into the composition and catalytic performance of VOx-Ga/γ-Al2O3 for the oxidative dehydrogenation of propane to propene - Kandasamy, Prabu; Gawali, Sheetal; Venugopalan, Aswathy Thareparambil; Manikandan, Marimuthu; Mekala, Siva Prasad; Shelke, Ankita; Ajithkumar, Thalasseril G.; Bhatte, Kushal; Raja, Thirumalaiswamy (New Journal of Chemistry, 2024)
Oxidative dehydrogenation (ODH) of propane is a promising alternative route for propene production. In this work, we developed a series of vanadium and gallium oxides supported on gamma-Al2O3 catalysts by an incipient wetness impregnation method. Among the employed catalysts, the VGA-2 showed superior catalytic activity, and the catalyst was demonstrated for longevity in ODH of propane with a stable activity using a continuous flow fixed bed reactor at 400 degrees C. H-2-TPR and UV-visible spectra showed the presence of highly dispersed monomeric VOx species with tetrahedral coordination geometry, which influences product selectivity. The characterization results also conferred that the redox nature of vanadium (V5+ and V4+) oxide and higher V5+ content on the surface of the VGA-2 catalysts are more favourable for C-H activation. In addition, the pyridine-FTIR and Ga-71 solid-state NMR studies further substantiated the presence of Lewis acid sites and tetrahedrally coordinated Ga3+Ox species that are highly responsible for the ODHP activity, respectively. Furthermore, in situ-DRIFTS studies conferred that the propane adsorption at ambient temperature showed the formation of intermediate propoxide species with the evolution of sigma-bonds and with further increase in the temperature to 325 degrees C; the stretching vibrations of the =C-H and -C-H bonds in the propylene molecule were observed. The spent catalysts were also analyzed by thermogravimetric analysis, where the optimized catalyst (VGA-2) showed the least coke deposition.

Temperature-controlled hydrothermal synthesis of α-MnO2 nanorods for catalytic oxidation of cyclohexanone - Jha, Ratnesh Kumar; Manikandan, Marimuthu; Prabu, Marimuthu; Vineeth, Nidhi R.; Dharmalingam, Praveen; Archana, Ramakrishnan; Harsha, Murudappa; Shankar, Sonu Ram; Bhatte, Kushal; Raja, Thirumalaiswamy (CHEMPLUSCHEM, 2024)
Keywords: Adipic Acid; conversion; MANGANESE OXIDES

Deciphering the intricate mechanisms behind the selective oxidation of methane to C1 and C2 oxygenates over FeAu/γ-Al2O3 catalysts - Prabu, Marimuthu; Manikandan, Marimuthu; Rengam, B. Sathya Sai; Ramakrishnan, Archana; Raja, Abhishekram; Urkude, Rajashri R.; Ghosh, Biplab; Varghese, Jithin John; Raja, Thirumalaiswamy (Chemical Engineering Journal, 2025)
In this work, we demonstrate an eco-benign synthesis protocol for preparing gold nanoparticles and the role of the strong interaction between gold nanoparticles and iron oxide in FeAu/gamma-Al2O3 catalysts that render it an anionic (Au delta-) character while tailoring them in a smaller size. The multifunctional FeAu/gamma-Al2O3 catalyst selectively produces ethanol (95 % selectivity, similar to 240 mu mol(-1) cat) at a mild temperature of 75 degrees C without the addition of co-reactants during liquid phase methane oxidation with molecular oxygen. Conversely, Au/gamma-Al2O3 and Fe/gamma-Al2O3 catalysts exhibited high selectivity for CH3OH and HCHO. A high dispersion accompanied by strong electronic interaction between the Au delta–FeOx, as corroborated by diverse techniques, enables methane activation across the interface and coupling on the gold nanoparticles, which are responsible for the markedly improved formation of ethanol. Furthermore, in situ DRIFTS studies and DFT investigations point to a reaction mechanism of coupling of CH2OH and CH3 intermediates as the most likely route for ethanol formation.
Keywords: Anionic gold catalysts; Au-FeOx synergism; C-H bond activation; Ethanol; Methane oxidation; Methanol

Facile and eco-friendly synthesis of Mn2O3 nanoparticles via microwave-assisted glycerol-thermal method - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Gehlot, Bhavika; Kamble, Aditi; Manikandan, Marimuthu; Bhosale, Hritvik; Vaishnav, Vishal; Rathod, Rutik; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Chemical Sciences, 2025)
Microwave-assisted efficient synthesis of nanosized manganese oxide (Mn2O3) is reported using glycerol and manganese acetate. Glycerol in this reported methodology acts as an efficient solvent for this nanomaterial synthesis under microwave radiation. This reported method enables the synthesis of nanosized Mn2O3 without further use of additives, stabilizers, and bases other than glycerol and manganese precursor. Glycerol is a renewable biomaterial derived nonvolatile and nontoxic, safe solvent. It has a high boiling point and dielectric constant, which makes it an ideal solvent for microwave synthesis. The synthesized nanosized Mn2O3 was analyzed by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. We examined the catalytic properties of as-synthesized Mn2O3 for cinnamyl alcohol oxidation to cinnamaldehyde. In this oxidation activity experiment, nanosized Mn2O3 exhibits good conversion and selectivity towards the desired product. We also made an attempt to understand the probable mechanism of nanomaterial formation and found some conclusive evidence to support it. This research methodology is facile, energy efficient, and involves minimum chemicals for synthesis. It makes this reported methodology not only economically attractive but also environmentally friendly, which aligns well with green chemistry principles.
Keywords: Glycerol; green chemistry; Nanosized Mn2O3; nanostructured catalysis

Hydrodeoxygenation of guaiacol to cyclohexanol using noble metal-supported Ni-based perovskite-derived catalysts - Marimuthu, Prabu; Raja, Thirumalaiswamy; Vinu, Ravikrishnan (ChemCatChem, 2025)
This study focuses on the role of noble metal-doped Ni-based perovskites, specifically LaNiO3 and NiTiO3 catalysts in the hydrodeoxygenation (HDO) of guaiacol. The findings demonstrate that reduced Ru-LaNiO3 catalyst achieved superior performance with 100% guaiacol conversion and a 75% selectivity toward cyclohexanol, compared to reduced Ru-NiTiO3, which achieved only 43% conversion and 25% cyclohexanol selectivity under identical conditions (240 degrees C, 30 bar H2, and 4 h). High-resolution transmission electron microscopic (HR-TEM) analysis reveals that LaNiO3-supported catalysts exhibit better metal dispersion and smaller nickel nanoparticle sizes compared to NiTiO3-supported counterparts. X-ray photoelectron spectroscopy (XPS) analysis shows that the reduction of nickel and noble metals is more facile on LaNiO3. Additionally, the O 1s XPS profile for reduced Ru-LaNiO3 indicates a higher proportion of lattice oxygen (OLat similar to 79%) and a lower proportion of oxygen vacancies (OVac similar to 21%) compared to other catalyst systems. The optimized OLat/OVac ratio is shown to be critical for the effective HDO of guaiacol. In situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) demonstrates a high HDO reaction rate using reduced Ru-LaNiO3 than reduced Ru-NiTiO3, with cyclohexanol formation attributed to the keto-enol tautomerization pathway. Overall, this study underscores the critical roles of oxygen vacancies, metal dispersion, and metal-metal oxide interactions in the HDO of guaiacol.
Keywords: Cyclohexanol; Guaiacol; Hydrodeoxygenation; In-situ DRIFT; Ni-based perovskites

An unique microwave-assisted approach for synthesis of nanosized Fe3O4 as a catalyst in transfer hydrogenation of furfural - Bhatkar, Akash; Yadav, Akash; Gehlot, Bhavika; Rathod, Rutik; Mane, Samruddhi; Gawande, Vaishnavi; Bhosale, Hrtivik; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Research on Chemical Intermediates, 2025)
In this manuscript, we report an unique, one pot, one step synthesis of Fe3O4 nanoparticles. The protocol for synthesis of nanosized Fe3O4 was developed using only Benzyl Amine and Fe(II)acetate precursor via microwave route. Microwave route enables the synthesis of Fe3O4 nanoparticles in short duration and eliminates the need of several chemicals. These salient features make the entire synthetic process environment benign as per green chemistry principles. The morphology and other properties of synthesized nanoparticles were studied by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy analysis (XPS), Raman spectroscopy, Field Emission Scanning Electron Microscopy (FE-SEM), and High-Resolution-Transmission Electron Microscopy (HR-TEM). As-synthesized Fe3O4 nanoparticles exhibit efficient catalytic transfer hydrogenation of furfural using isopropanol as the solvent and hydrogen source, and provide furfuryl alcohol in good yield. This nanosized Fe3O4 was easily removable using magnet and exhibits good reusability. It is observed that acidic-basic sites of nanosized Fe3O4 play a vital role in catalytic transfer hydrogenation reaction.
Keywords: catalytic transfer hydrogenation; Furfural to furfuryl alcohol; green synthesis; Magnetically separable catalyst; Nanosize Fe3O4

Enhancing Ru dispersion and catalytic stability via nitrogen-doped mesoporous carbon supports for biomass-derived FDCA production - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Pandey, Pragati; Raja, Abhishekram; Manikandan, Marimuthu; Raja, Thirumalaiswamy (Inorganic Chemistry Communications, 2026)
The rational design of efficient and selective nanostructured catalysts represents a key strategy for transforming biomass-derived feedstocks into value-added chemicals and fuels. 5-hydroxymethylfurfural (HMF) has emerged as one of the most promising platform chemicals due to its versatile reactivity and potential to be transformed into a wide range of value-added products. Herein, we report the preparation of Ru nanoparticles supported on both N-free and N-doped mesoporous carbon via wetness impregnation, and their application in the catalytic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) under mild reaction conditions. The 3wt% Ru-NMC-2 catalyst afforded complete HMF conversion with 83% yield of FDCA at 110 degrees C within 10 h under 10 bar O2. Our research reveals that the nitrogen content in the carbon matrix imparts basicity to the catalyst support, stabilizing smaller Ru metal nanoparticles and helping to maintain a higher metal dispersion (66%), thereby enhancing FDCA yield and turnover frequency. Furthermore, XPS analysis demonstrated that N doping in the carbon matrix would aid in stabilizing the higher availability of metallic Ru compared with nitrogen-free counterparts. The recyclability of the catalyst was demonstrated over 5 cycles, and it exhibited satisfactory catalytic performance towards FDCA yield.
Keywords: 5-Furandicarboxylic acid (FDCA); 5-hydroxymethylfurfural (HMF); biomass valorization; Metal-support interactions; nitrogen-doped carbon; Ruthenium catalysts